The Evolution of Efficiency in Costa Rican Banking System 2005-2015: Evidence from Data Envelopment Analysis - Salas-Alvarado, Andrés (2016)
In this study the technical and scale efficiency of Costa Rican banking system is estimated for the 2005-2015 period, through the Data Envelopment Analysis (DEA). The estimations are within the approach of variable returns to scale with slacks developed by Banker, Charnes, and Cooper (1984) and the constant returns to scale approach developed by Charnes, Cooper, and Rhodes (1978). Efficiency scores were estimated annually for each bank to get the average for state banks, private banks, and the whole system. The inputs and outputs considered in the DEA model were defined through the intermediation approach. Through the application of DEA was concluded that a) for the whole system there are no clear efficiency improvements during the period analyzed, b) the most efficient banks were Banco BCT and Banco General, c) private banks were on average more efficient than state banks and d) the goods of net use were, on average, the input with bigger slack.